Filming the In-between: Studying the Representation of Cultural Identities of Immigrant Families In Canadian and Quebec Cinema - Decock, Olena (Université d'Ottawa / University of Ottawa, 2012)
With a statistical rise in visible, audible and cultural minorities in Canada, the importance of recognizing the relationship between immigrants, culture and identity as constructed in collective discourse becomes paramount. Through hermeneutic and sociocritical paradigms, this research applies a constructionist approach to qualitatively analyze representations of cultural identities in Canadian and Quebec films projecting intergenerational conflicts within immigrant families. From these analyses, five tendencies were elicited: guilt, displacement, in-betweenness, reflections on Canadian society, and heterogeneous perspectives. While deconstructing cultural identity portrayals remains crucial, it is equally important to study these systems of meaning within production. The research is extended through the appendaged short film,Tracing Shadows, a glimpse into the voices of the Ukrainian diaspora in Canada. Both textual analyses and the filmic creation demonstrate the symbiotic connection between society and culture, nurtured within collective identity narratives’ depictions of time and space.
Keywords: identity; diaspora; sociocritical analysis; semiotics; Canadian and Quebec cinema